Obtenção de água de reúso a partir da adsorção de corantes em lodo de esgoto - Oliveira, Bianca (2015)
The scarcity and contaminate on of hydrous bodies are, because the water is an essential element for all types of life. One of the responsible for the contaminate of the water is the textile industry. The dyestuff is a contaminant arising of that segment, that are dyestuff soluble and not soluble, because of that your treatment are complex. One alternative for the removal of this is the utilization of adsorbents. The are some types of adsorbents such as activated carbon zeolitas, silica gel and activated alumina. However, because of the high cost of some adsorbents, like activated carbon, if search alternatives compounds. Another choice is the slime, from the effluent treatment plants (ETPs). That material this material is accessible and abundant, could became a problem on the ETPs. Therefore, the reuse of mud as adsorbent only have to contribute with an environment. For the production of the mud as adsorbent two essential steps, the pyrolysis and the chemical treatment. The objective of the pyrolysis it is increase in surface area. However, chemical treatment have the propose active the compost for adsorption happen. For to be active chemically activated, in this work, was used solutions of sulphuric acid (0,2 mol∙L-1) and alumen of potassium (5% m/m). The treatments were analyzed aesthetically, and the factorial design for both 2² (factors: chemical treatment and pH). Was determined the treatment more efficient in the removal of mud chemically treated with sulphuric acid, pH 2. Kinetics and adsorption equilibrium experiments were performed, where the experimental data were fit to theoretical models isotherms and kinetics of adsorbing. The experimental data obtained for isotherms was adjusted to de models of Langmuir e Freundlich. Using the software Origin curves were obtained, values de R² and parameters de both models, with this, if observed that the Freundlich was the model witch that best adapted to the adsorbing (R² = 0,802). As for the kinetic the experimental results were adjusted to the models of pseudo-first-order and pseudo-second-order, where the best fit was found the pseudo-second-order (R² = 0,999). By analyzing the characterization physico-chemically the surface of the adsorbing if obtained it is acidic, because the pHpcz found was 4,2 and the presentes grups functional was in the most part acids. Beyonf the contamination, other problem found in the industry is the high volume of water using in the process. Because of that, the water reuse is alternative to be applied in this environment. When performing the analysis to the environmental and technical feasibility of reuse if had that the treated effluent possess features which allows you to reuse water production in the textile industry, but only in the ironing process, provided that pH adjustment is made, because the value found for the iron and manganese on the sample not suitable for others process.